CSR Disclosure and Financial Misstatement Risk in Indonesian Mining Firms - Erlinda Ramadhani Permata Putri; Verina Purnamasari (Universitas Islam Sultan Agung, Faculty of Economic and Business, Accounting Dept, 2026)
Abstract This study examines the association between prior-year corporate social responsibility (CSR) disclosure and financial misstatement risk among Indonesian mining firms. The sample consists of 242 firm-year observations from 49 listed mining firms during 2020–2024. CSR disclosure is measured using a Global Reporting Initiative-based disclosure index, while financial misstatement risk is estimated using the Dechow F-Score. The analysis employs a Common Effect Model with firm-clustered robust standard errors. The main regression shows that CSR disclosure is positively associated with financial misstatement risk (coefficient = 0.315; p = .014). Profitability and firm size also have positive and significant effects, while leverage has a negative and significant effect. The model explains 28.74% of the variation in misstatement risk and is jointly significant. However, alternative specifications produce a negative but weakly significant CSR coefficient, indicating that the CSR result is sensitive to model specification. These findings suggest that disclosure quantity alone cannot be interpreted as a stable indicator of financial reporting integrity.